Penerapan Simulasi Pada Perusahaan Berbasis Lean - Arie Respama Putra (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2011)
Lean Manufacturing is an approach to make the system efficient using the waste reduction. The approach is conducted by understanding the general picture of the company using the flow of information and materials in the production floor by creating value stream mapping. Lean Manufacturing is not only useful in the production floor; however it can be implemented in various levels of company organization. However the simulation is a totally different discipline which can support applications in other disciplines. Using the simulation, the implementation process of Lean Manufacturing can be conducted precisely and result in more alternative solutions in the production processes. Simulation has many types of tools, of which the most popular one is the Pro Model. The tool tries to illustrate the model from the actual production process by conducting several simulations until the optimum solution can be achieved for the Lean Manufacturing.